Effective project management : guidance and checklists for engineering and construction - Ward, Garth G. F. (Wiley-Blackwell, John Wiley & Sons Ltd, 2018)
"This book provides the project manager with a quick reference and guide to tackling any situation or problem that they may be facing, without the need for extensive background research. It covers project initiation and execution, as well as the personal skills and techniques required to effectively manage projects"--